Application of a Weight of Evidence Approach for Monitoring Complex Environmental Scenarios: the Case-Study of Off-Shore Platforms - Regoli, Francesco; d’Errico, Giuseppe; Nardi, Alessandro; Mezzelani, Marica; Fattorini, Daniele; Benedetti, Maura; Di Carlo, Marta; Pellegrini, David; Gorbi, Stefania (Frontiers in Marine Science, 2019)
Multidisciplinary investigations based on integration of chemical and biological measurements, represent an added value to monitoring and management protocols, and their use is recommended by European Directives to evaluate environmental status of aquatic ecosystems. Nonetheless, assessing the overall significance of results from different studies is still a challenge. This work was aimed to present a quantitative Weight Of Evidence (WOE) model (Sediqualsoft) to integrate huge amounts of heterogeneous data and to validate this approach in complex monitoring scenarios. Using the case-study of off-shore platforms in the Adriatic Sea, procedures are presented to elaborate different typologies of data (lines of evidence, LOEs), including chemical characterization of sediments, bioavailability, biomarkers, ecotoxicological bioassays and benthic communities. These data are initially evaluated by logical flowcharts and mathematical algorithms, which provide specific hazard indices for each considered LOE, before their weighting and integration in an environmental risk index. The monitoring study selected for the WOE elaboration consisted on chemical analyses of trace metals, aliphatic hydrocarbons, polycyclic aromatic hydrocarbons carried out on 60 sediment samples; the same samples were characterized for the status of benthic communities; bioavailability of metals from sediments was assessed at laboratory conditions on the polychaete Hediste diversicolor, while bioaccumulation of inorganic and organic chemicals and biomarkers were measured in native and transplanted mussels; ecotoxicological properties of sediments were evaluated through a battery of bioassays determining algal growth of the diatom Phaeodactylum tricornutum, bioluminescence of the marine bacterium Vibrio fischeri, survival of the copepod Acartia tonsa and embryotoxicity of sea urchin Paracentrotus lividus. Almost 7000 analytical results were elaborated and summarized in specific hazard indices. The WOE integration of multiple typologies of data allowed more robust and weighted conclusions compared to the use of individual LOEs, highlighting the feasibility of this procedure for multidisciplinary monitoring and risk assessment approaches. On a practical side, the WOE evidences also suggested a revision of actual monitoring procedures. The proposed WOE model appears a useful tool to summarize large datasets of complex data in integrative indices, and to simplify the interpretation for stakeholders and decision makers, thus supporting a more comprehensive process of “site-oriented” management decisions.